2007
DOI: 10.1007/s10495-007-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile toxin A-induced apoptosis is p53-independent but depends on glucosylation of Rho GTPases

Abstract: Clostridium difficile toxin A (TcdA) is one of two homologous glucosyltransferases that mono-glucosylate Rho GTPases. HT29 cells were challenged with wild-type and mutant TcdA to investigate the mechanism by which apoptosis is induced. The TcdA-induced re-organization of the actin cytoskeleton led to an increased number of cells within the G2/M phase. Depolymerization of the actin filaments with subsequent G2/M arrest, however, was not causative for apoptosis, as shown in a comparative study using latrunculin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
93
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 44 publications
9
93
0
Order By: Relevance
“…41 Contributing to the heterogeneity of LatB effect in cells of different origin, our data also show that HBMEC apoptosis induced by LatB, which was mediated by c-Abl, was not a universal effect because tumor cell lines we and others examined did not exhibit LatB-induced apoptosis. 30 Further specificity of the role of c-Abl in HBMEC apoptosis is suggested because, whereas LatB-induced apoptosis in HBMECs was inhibited by STI-571 and siRNA to c-Abl, etoposide-induced PARP cleavage was not inhibited by STI-571, and etoposide-and vincristine-induced caspase-8 cleavage was also not inhibited by siRNA to c-Abl (supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…41 Contributing to the heterogeneity of LatB effect in cells of different origin, our data also show that HBMEC apoptosis induced by LatB, which was mediated by c-Abl, was not a universal effect because tumor cell lines we and others examined did not exhibit LatB-induced apoptosis. 30 Further specificity of the role of c-Abl in HBMEC apoptosis is suggested because, whereas LatB-induced apoptosis in HBMECs was inhibited by STI-571 and siRNA to c-Abl, etoposide-induced PARP cleavage was not inhibited by STI-571, and etoposide-and vincristine-induced caspase-8 cleavage was also not inhibited by siRNA to c-Abl (supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The large T antigen binds several cellular factors, including p53, a tumor suppressor known to regulate cell cycle, mitotic division, and apoptotic cell death pathways. There are conflicting reports regarding the function of p53 in TcdA-induced apoptosis (35,45). One study using a nontransformed colonic cell line concluded that TcdA-induced apoptosis is dependent upon p53 function (45).…”
Section: Discussionmentioning
confidence: 99%
“…This inactivation has been linked to a cell rounding or cytopathic effect (CPE) (21)(22)(23)(24) and to an apoptotic cytotoxic effect (25)(26)(27)(28)(29)(30)(31)(32)(33). In tissue culture models, the apoptotic effects of TcdA and TcdB occur at toxin concentrations of picomolar or lower and are evident at 24 to 48 h postintoxication (26,28,29,(34)(35)(36). TcdB also induces a glucosyltransferase-independent necrosis that is mediated by the assembly and activation of the NADPH oxidase (NOX) complex, subsequently producing high levels of reactive oxygen species (ROS) (34,(37)(38)(39)(40).…”
mentioning
confidence: 99%
“…The proteins are homologous glucosyltransferases that inactivate small GTPases of the Rho/Rac family. The resulting disruption in signaling causes a loss of cell-cell junctions, dysregulation of the actin cytoskeleton, and apoptosis (4,5).…”
mentioning
confidence: 99%